2022
DOI: 10.1186/s12889-022-13104-0
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable risk factors in adults with and without prior cardiovascular disease: findings from the Indonesian National Basic Health Research

Abstract: Backgrounds The majority of risk factors for cardiovascular diseases (CVDs) are modifiable. Continuous monitoring and control of these factors could significantly reduce the risk of CVDs-related morbidity and mortality. This study estimated the prevalence of modifiable risk factors in Indonesia and its co-occurence of multiple risk factors stratified by prior CVDs diagnosis status and sex. Methods Adult participants (> 15 years, N = 36,329, 57% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 40 publications
1
16
0
1
Order By: Relevance
“…Behavioral factors, which mainly include diet-related issues, tobacco, and alcohol use, and physical activity that can otherwise be defined as a lifestyle, demonstrate a significant impact on the possibility and frequency of disease and can determine life expectancy. According to the current data, compared to metabolic and environmental conditions, these factors significantly impact human health [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral factors, which mainly include diet-related issues, tobacco, and alcohol use, and physical activity that can otherwise be defined as a lifestyle, demonstrate a significant impact on the possibility and frequency of disease and can determine life expectancy. According to the current data, compared to metabolic and environmental conditions, these factors significantly impact human health [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the front-line in delivering health care services, Puskesmas plays a significant role in preventing and controlling disease, including CVD, in the community. Although the prevalence of CVD and its risk factors in Indonesia are high in both primary and secondary prevention populations [15], our study showed a low number of patient visits per month for hypertension, diabetes and CVD, with decreasing trends for the average number of patient visits in 2020.…”
Section: Discussionmentioning
confidence: 52%
“…[33] Peluang bisnis industri pelayanan kesehatan sangat menjanjikan dengan situasi perubahan pola gaya hidup masyarakat yang juga mempengaruhi pola kesehatan masyarakat. [34] Dengan kondisi kepemilikan masyarakat Indonesia terhadap asuransi kesehatan membuat semakin meningkatnya volume pelayanan kesehatan dengan nilai transaksi yang cukup tinggi.…”
Section: Tinjauan Teoritis Tantangan Dan Peluang Industri Pelayanan K...unclassified